Establishing sexual dimorphism: conservation amidst diversity? - Zarkower, D. (Nature Reviews. Genetics, 2001)
The molecular mechanisms that control sexual dimorphism are very different in distantly related animals. Did sex determination arise several times with different regulatory mechanisms, or is it an ancient process with little surviving evidence of ancestral genes? The recent identification of related sexual regulators in different phyla indicates that some aspects of sexual regulation might be ancient. Studies of sex-determining mechanisms are beginning to reveal how sexual dimorphism arises and evolves.